1998
DOI: 10.1183/09031936.98.12061463
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenetic basis of environmental lung disease: lessons from the berylliosis model

Abstract: The role of genetic factors has been hypothesized in the pathogenesis of a number of chronic inflammatory lung diseases. The genes of the major histocompatibility complex (MHC) locus on human chromosome 6 have been identified as important determinants in diseases caused both by inorganic and organic compounds such as beryllium, gold, acid anhydrides, isocyanates and grass pollens. Since many environmental factors are the determinants of the immunopathogenesis of asthma, pulmonary granulomatous disorders, hyper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
58
0
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(59 citation statements)
references
References 109 publications
0
58
0
1
Order By: Relevance
“…Genetic susceptibility to both beryllium sensitization and CBD has been linked to particular alleles of the MHC class II molecule, HLA-DP (13)(14)(15)(16)(17). In particular, susceptibility has been most strongly associated with HLA-DPB1 alleles that encode a negatively charged glutamic acid (E) at position 69 (Glu 69 ) of the ␤-chain.…”
Section: Hronic Beryllium Disease (Cbd)mentioning
confidence: 99%
“…Genetic susceptibility to both beryllium sensitization and CBD has been linked to particular alleles of the MHC class II molecule, HLA-DP (13)(14)(15)(16)(17). In particular, susceptibility has been most strongly associated with HLA-DPB1 alleles that encode a negatively charged glutamic acid (E) at position 69 (Glu 69 ) of the ␤-chain.…”
Section: Hronic Beryllium Disease (Cbd)mentioning
confidence: 99%
“…Susceptibility to CBD has been associated with particular alleles of the class II MHC molecule, HLA-DP (5)(6)(7)12). In the present study, we determined whether proliferation of beryllium-specific CD4 ϩ T cells from the lungs of CBD patients involved presentation by HLA-DP.…”
mentioning
confidence: 93%
“…Although E69 is a strong marker of sensitization and disease, questions remain whether certain alleles confer greater risk of disease than others. Some studies have suggested that a greater prevalence of a non-*02 E69 variant is found in CBD and BeS (8,(10)(11)(12)(13), whereas others have not (14,15). Since the time of these first studies of associations between the HLA-DPB1 gene and CBD, many new alleles have been identified owing to improvements in typing methods.…”
mentioning
confidence: 99%